Literarisch-linguistische Besonderheiten in Wolfgang Hildesheimers Selbst-Übersetzungen - Salvato , Lucia (Linguistik Online, 2021)
This paper presents a linguistic analysis of a lesser known part of the written production of German writer and artist Wolfgang Hildesheimer (1916–1991). The insight into his two speeches, delivered in English and self-translated into German, has two aims. First, to analyze their most peculiar linguistic features. Second, to highlight Hildesheimer’s linguistic awareness and his extensive activity with languages and with their variations. Thanks to his bilingualism, he used to explore language variations and often realized some in a very peculiar way. The features highlighted in the analysis concern above all literal equivalents, the translation of foreign and loan words, of metaphors and idioms. This aims to emphasize Hildesheimer’s ability to deal with languages and their qualities.